2013
DOI: 10.3390/rs5116096
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Properties of ENVISAT ASAR and QuikSCAT Surface Winds in the North Sea

Abstract: Spectra derived from ENVISAT Advanced Synthetic Aperture Radar (ASAR) and QuikSCAT near-surface ocean winds are investigated over the North Sea. The two sensors offer a wide range of spatial resolutions, from 600 m to 25 km, with different spatial coverage over the area of interest. This provides a unique opportunity to study the impact of the spatial resolution on the spectral properties of the wind over a wide range of length scales. Initially, a sub-domain in the North Sea is chosen, due to the overlap of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These are attributed to the lack of ability in ERA5 to properly resolve the coastal atmospheric flow phenomena.. From the spatial resolution perspective, it is obvious that SAR resolves the finest spatial detail than other products. From spectral analysis of SAR vs. scatterometer winds, it was found that SAR resolves around 4 km features and scatterometer around 25 km features (Karagali et al, 2013b). The latter is comparable in scale to what the WRF model at 3 km grid spacing resolves, i.e.…”
Section: Comparison Of Offshore Mean Wind Speed Maps At 100m Heightmentioning
confidence: 78%
“…These are attributed to the lack of ability in ERA5 to properly resolve the coastal atmospheric flow phenomena.. From the spatial resolution perspective, it is obvious that SAR resolves the finest spatial detail than other products. From spectral analysis of SAR vs. scatterometer winds, it was found that SAR resolves around 4 km features and scatterometer around 25 km features (Karagali et al, 2013b). The latter is comparable in scale to what the WRF model at 3 km grid spacing resolves, i.e.…”
Section: Comparison Of Offshore Mean Wind Speed Maps At 100m Heightmentioning
confidence: 78%
“…With regards to spatial resolution, it is obvious that SAR resolves finer spatial detail than other products. From spectral analysis of SAR vs. scatterometer winds, it was found that SAR resolves around 4 km features, and the scatterometer resolves around 25 km features (Karagali et al, 2013b). The latter is comparable in scale to what the WRF model at 3 km grid spacing resolves, i.e.…”
Section: Comparison Of Offshore Mean Wind Speed Maps At 100 M Heightmentioning
confidence: 83%
“…The SAR-derived wind maps at 1 × 1 km resolution have much spatial detail. According to [44], the spectral density in Envisat ASAR WSM wind maps is high. Thus, SAR wind fields observe small-scale variability of ocean surface winds.…”
Section: E Discussionmentioning
confidence: 99%